MAGNETOHIDRODINAMIKA FLUIDA MIKROPOLAR PADA LAPISAN BATAS MELEWATI PELAT DATAR YANG DIPENGARUHI KONVEKSI CAMPURAN - Jason Otniel Dharmanta; Basuki Widodo; Dieky Adzkiya; Chairul Imron (UPT Penerbitan Universitas Jember, 2022)
This study considers about the magnetohydrodynamics of micropolar fluids in the boundary layer passing through a flat plate which is affected by mixed convection. The governing equations are obtained from the continuity, momentum, energy equations, and Maxwell’s equation. The micropolar fluid passes through the flat plate, flowing from the below. The obtained dimensional equations are then transformed into non-dimensional equations using non-dimensional variables, then transformed into similarity equations. The similarity equations can be introduced using stream functions, that produce non-linear partial differential equations. The equations are then solved by Keller-Box method. The numerical results obtained are in the form of temperature and fluid velocity profiles with variations in magnetic parameters, micropolar parameters, porosity parameters and Prandtl numbers. The numerical simulation results show that the greater the magnetic parameter (), the micropolar parameter () and the porosity parameter (), respectively, then the speed decreases but the temperature increases. However, the variation of the Prandtl numbers () does not affect the speed. The greater the Prandtl number, the lower the temperature. Keywords: Flat plate, Keller-Box, magnetohydrodynamics, micropolar fluid